INFRARED SPECTRAL ANALYSIS OF GYPSUM CONCRETE MATERIALS (Spectrum Journal of Innovation, Reforms and Development, 2026)
This study investigates the infrared spectral characteristics of gypsum concrete materials prepared using lime waste and Redispersible Polymer Powder (RPP). The objective was to determine the changes occurring in the mineralogical and chemical composition of gypsum concrete after the addition of 1% RPP. Infrared spectroscopy was applied to compare gypsum concrete specimens prepared without RPP and with 1% RPP. The obtained spectra revealed significant changes in the absorption bands located at 2343–2358 cm⁻¹, 2850–2922 cm⁻¹, and 3390 cm⁻¹. The appearance of new absorption peaks and the increase in their intensity indicate the formation of new mineral phases and stronger chemical bonds. The bands observed in the regions of 596–665 cm⁻¹, 877–1111 cm⁻¹, and 1465–1683 cm⁻¹ correspond to silicates, carbonates, and water-related functional groups. The increase in the intensity of OH-group vibrations and polymer-related absorption bands confirms the enhanced degree of polymerization and hydration in the modified gypsum concrete. The results demonstrate that the incorporation of 1% RPP into lime-waste-based gypsum concrete contributes to the formation of high-strength compounds and improves the structural properties of the material.